Evaluation of a novel pre‐treatment model of nutrition care for patients with head and neck cancer receiving chemoradiotherapy. Issue 2 (2nd December 2021) - Blake, Claire; Edwards, Anna; Treleaven, Elise; Brown, Teresa; Hughes, Brett; Lin, Charles; Kenny, Lizbeth; Banks, Merrilyn; Bauer, Judy
Abstract: Aims: Weight loss and malnutrition occur frequently in patients with head and neck cancer and are associated with reduced survival. This pragmatic study aimed to determine the effect of a novel pre‐treatment model of nutrition care on nutrition outcomes for patients with head and neck cancer receiving chemoradiotherapy. Methods: This health service evaluation consisted of an evaluation of the new model of care implementation (Phase 1) and an evaluation of patient outcomes (Phase 2) in pre‐ and post‐implementation cohorts ( n  = 64 and n  = 47, respectively). All Phase 2 patients received a prophylactic gastrostomy. The new model of care consisted of dietary counselling and commencement of proactive supplementary enteral nutrition via a prophylactic gastrostomy, in addition to normal oral intake, prior to treatment commencement. Nutrition outcomes were collected at baseline (pre‐treatment) and 3 months post‐radiotherapy completion. Results: The new model of care was successfully incorporated into practice with high referral (96.5%) and attendance (91.5%) rates to the counselling session, and high adherence rates to proactive tube feeding (80.9%). Patients in the post‐implementation cohort had less weight‐loss (1.2%; p  = 0.338) and saw less of a decline in nutritional status compared to patients in the pre‐implementation cohort (23% vs. 30%, respectively; p  = 0.572), deemed clinically important. However, patients still experienced critical weight loss overall (mean 9.9%). Conclusion: Pre‐treatment nutrition care was feasible in standard clinical practice and demonstrated clinically relevant outcome improvements for patients. Future high‐quality research is warranted to investigate further multidisciplinary strategies to attenuate weight‐loss further, inclusive of patient‐reported barriers and enablers to nutrition interventions.